First occurrence of Cloudina carinata Cortijo et al., 2010 in South America, Tamengo Formation, Corumbá Group, upper Ediacaran of Midwestern - ADÔRNO, Rodrigo Rodrigues (2019)
It is herein presented the unprecedented occurrence of Cloudina carinata Cortijo et al., 2010 in the American continent. This new occurrence expanded the geographic distribution of this species, until now reported from sections in Spain and Siberia. The assembled biomineralizing metazoans Cloudina carinata, Cloudina lucianoi (Beurlen & Sommer, 1957) and Corumbella werneri Hahn et al., 1982 are presented for the first time from the Tamengo Formation, Corumbá Group, Porto Figueiras section, Corumbá Municipality, Mato Grosso do Sul State, Brazil. This new occurrence could be employed as an additional biostratigraphic tool for international correlation of the terminal Ediacaran, as well as for palaeobiogeographic and palaeoecologic reconstructions.